2023
DOI: 10.1111/apt.17614
|View full text |Cite
|
Sign up to set email alerts
|

Severe hepatitis B flares with hepatic decompensation after withdrawal of nucleos(t)ide analogues: A population‐based cohort study

Abstract: Background: Finite nucleos(t)ide analogue (NUC) therapy has been proposed as an alternative treatment strategy for chronic hepatitis B (CHB). Aim:To quantify the incidence of severe hepatitis flares following NUC cessation in everyday clinical practice.Methods: This population-based cohort study enrolled 10,192 patients (male 71.7%, median age 50.9 years, cirrhosis 10.7%) who had received first-line NUCs for at least 1 year before discontinuing treatment. The primary outcome was severe flare with hepatic decom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Hsu et al reported the real‐world safety data of nucleoside analogue discontinuation in a heterogeneous population involving 10,192 patients with CHB of whom 10.7% had cirrhosis and 4.6% had a prior history of liver failure 6 . These patients were given a nucleoside analogue, which was subsequently stopped according to local reimbursement policies.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Hsu et al reported the real‐world safety data of nucleoside analogue discontinuation in a heterogeneous population involving 10,192 patients with CHB of whom 10.7% had cirrhosis and 4.6% had a prior history of liver failure 6 . These patients were given a nucleoside analogue, which was subsequently stopped according to local reimbursement policies.…”
Section: Figurementioning
confidence: 99%
“…5 Hsu et al reported the real-world safety data of nucleoside analogue discontinuation in a heterogeneous population involving 10,192 patients with CHB of whom 10.7% had cirrhosis and 4.6% had a prior history of liver failure. 6 These patients were given a nucleoside analogue, which was subsequently stopped according to local reimbursement policies. The primary outcome was severe flare with hepatic decompensation, defined as serum alanine aminotransferase >5 times upper limit of normal plus hyperbilirubinaemia plus coagulopathy;…”
Section: Editorial: Mitigating the Risk Of Severe Hepatitis Flare Fol...mentioning
confidence: 99%
“…We read with great concern of the study by Hsu et al 1 on severe hepatitis flare with decompensation after cessation of nucleos(t)ide analogue (NUC) based on a large database of patients with chronic hepatitis B (CHB) infection in Taiwan. The study showed 4-year cumulative incidence of off-therapy hepatic decompensation and mortality/ liver transplantation 1.8% and 0.7%, respectively; the 4-year incidence of hepatic decompensation decreased to 1.3% in patients without evidence of cirrhosis and 1.1% in those adhering to a standardised stopping rule.…”
Section: Letter: Safety After Cessation Of Nucleos(t)ide Analogue The...mentioning
confidence: 99%
“…This article is linked to Hsu et al papers. To view these articles, visit https://doi.org/10.1111/apt.17614 and https://doi.org/10.1111/ apt.17657 Yao-Chun Hsu 1,2,3 Mindie H. Nguyen 4,5 Chun-Ying Wu 3,6 AP&T correspondence columns are restricted to invited editorials and letters discussing papers that have been published in the journal. An invited editorial or letter must have a maximum of 500 words, may contain one table or figure, and should have no more than 10 references.…”
Section: N K Ed Co Ntentmentioning
confidence: 99%
“…1 However, we did not find an association between the antiviral regimen and hepatic decompensation from withdrawal flares in our study. 2 If Liu et al had reviewed LETTER TO THE EDITOR…”
mentioning
confidence: 99%